Kesiapan Perawat dalam Penanganan Kasus Trauma Multiple pada Skenario Simulasi Disaster Drill - Tondok, Santalia Banne; Yaroserai, Mais; Yunitasari, Veronika; Pasole, Fetty Yublika; Hoda, Ferdinandus Suban; Mahoklory, Serly Sani (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Natural disasters and mass accidents demand the preparedness of healthcare workers, particularly nurses, in handling multiple trauma. Disaster drill simulations are an effective training approach to measure and improve this preparedness. Objective: To assess the level of preparedness of nurses in handling multiple trauma through disaster drill simulation scenarios in a teaching hospital. Methods: This study used a quantitative descriptive design with a cross-sectional approach. A sample of 40 nurses participating in the disaster drill was drawn using purposive sampling. The research instruments consisted of a standardized questionnaire and an observation sheet based on a clinical skills checklist. Results: The results showed that 72.5% of nurses were categorized as "ready" in handling multiple trauma cases, with the highest scores in triage and airway management. However, 27.5% still showed unpreparedness in rapid decision-making and team coordination. Conclusion: The majority of nurses are well prepared for mass trauma scenarios, but regular training and simulation evaluation are still needed, particularly in communication and resource management during disasters.